High entropy ceramics: research trends and reviewing mechanical properties using computer vision techniques - Bijendra Kumar; Tapas Kumar Bhattacharya; Nipu Modak; Alok Mukherjee; Kingshuk Chatterjeee; Partha Haldar (Materials Research Express)
High entropy ceramics (HECs) represent a novel class of materials characterized by their unique multi-principal element compositions and exceptional properties. This study investigates the mechanical and thermal properties of high entropy ceramics through a comprehensive bibliometric analysis of 395 Scopus-indexed articles. Biblioshiny, VOSviewer and Gephi software are used to analyze different data linked with these articles. Data from abstracts are analyzed to identify properties like thermal conductivity, hardness, fracture toughness, etc Computer vision has been applied in data extraction and property characterization of HEC. Investigation reveals significant insights into the co-occurrence of keywords related to various mechanical properties, such as fracture toughness and compressive strength, alongside thermal characteristics like thermal conductivity. Visualizing these relationships highlights research clusters and identifies gaps in the current literature, paving the way for future exploration in this promising field.